(3GdHQhJhchdGJ hGdjghOjI hGdUgjhfjI (B/s - (3GdeSjQj, YHO GdhgGH s 1938-2008 ((3GdbGgQI (B:s (3OGQ GdTQhb ,s, 2005)
(3jQi GdOcJhQ GdeSjQj Cf GdHQhJhchdGJ hKjbI eRjaI, hPdc GSJfGOG Edi HYV GdMbGFb GdJj fTQJ Yf CUhdgG hef NdGd JMdjd GdfU ef GdOGNd(B. (3hgh jHjf aj gPg GdOQGSI Cf (B((3GdacQ GdHQhJhchdj(B) (3GdJBeQj acQ GNJRGdj, djSJ dg ebOQI JaSjQjI hdG MJi JYHhjI ; dCf cQg GdjghO GdPj jfWdb efg gPG GdNWGH jUH aj hGbY GdCeQ aj GdNfOb GdUgjhfj(B. (3aef jcQg GdjghO jbhe HGVWgGOge hGdJMQjV VOge, eeG jVWQge Edi (B((3GdNQhL(B) (3ef HdOge djJMhdhG Edi eSJhWfjf aj HdGOfG (B! (3ceG CffG, HJUhQfG Cf GdjghO ge (B((3GdSHH(B) (3ajeG jdMb HfG ef eUGFH, fJLGgd GdOYe GdCeQjcj GdTGed hGdeSJeQ ddLjH GdUgjhfj, hgh GdOYe GdPj jVef dg GdGSJeQGQ hGdHbGA(B.(3hGdUgjhfjI, ceG jbhd GdOcJhQ GdeSjQj, gj OYhI dJNdjU ChQHG ef GdjghO hJUOjQge Edi ecGf NGQLgG djhXahG dUGdMgG(B. (3hJHjf GdOQGSI Cf GdLPhQ GdMbjbjI ddUgjhfjI gh GdGSJYeGQ GdZQHj heYGOGI GdSGejI(B. (3hCf JQhjL GdHQhJhchdGJ jHK QhM GdgRjeI hjbhV QhM GdLgGO, hCf GdEUQGQ Ydi Cf GdjghOjI YHGQI Yf eLehYI ef GdUaGJ GdKGHJI GdJj jJhGQKgG GdjghO LjdG HYO Ljd jJfGai hJYGdje GdESdGe GdJj JPgH Edi Cf GdQPjdI eKd GdGSJbGeI eSCdI GNJjGQ hdjSJ eSCdI ejQGK(B. (3hJNJJe GdOQGSI HaUd Yf EHOGYGJ GfJaGVI (B1987 (3hGfJaGVI GdCbUi, hcja Cf eKd gPG GdEHOGY de jcf eecfG EdG HYO Cf faV GdefJaVhf Yf CfaSge ZHGQ GdNha hGdgRjeI(B.s
Keywords: (3GdjghOjI hGdSjGSIs; (3GdjghOjIs; (3GdUgjhfjIs